DIALOGUES BETWEEN IDENTITIES IN LUIS ALBERTO URREA’S THE HOUSE OF BROKEN ANGELS - Чернишова, Світлана (Taras Shevchenko National University of Kyiv (Ukraine), 2023)
In recent decades, there has been a noticeable increase in the prominence of writers who possess complex cultural orientations or participate in transnational exchanges. These authors reject the formerly narrow and restrictive identitarian labels, such as (im)migrant, colonial, postcolonial, ethnic, Commonwealth, or minority writers. They can no longer be confined to a single national framework, as they transcend such limitations. Transcultural writers have developed a transcultural sensibility. This sensibility is expressed through their writing, which encompasses impalpable elements such as sensitivities, imaginaries, and outlooks that cannot be measured or quantified. However, these elements are discernible through the author's choice of themes, characters, voice, setting, and the use of dialogue, plot construction, or language. Writers who explore beyond their native cultures or homelands tend to resist conventional classifications. Their intricate and fluid nature defies attempts to categorize them, even with the most sophisticated methods, as their works seem to evade definition and elude any attempt to fit them into a particular category or box. Luis Alberto Urrea’s The House of Broken Angels explores various complexities of identities. Particularly of Mexican-Americans who are often caught between two cultures. The characters in the novel struggle to find a sense of belonging in either Mexican or American culture. They often feel like they are not fully accepted in either culture and must navigate the complexities of being in between. The main character Big Angel was born in Mexico but has lived in the United States for most of his life. As the plot evolves, he struggles to reconcile his Mexican heritage with his American identity. The novel also discloses the complexities of family identity. The characters in the novel are part of a large, extended family, and their identity is deeply tied to their family history and traditions. The importance of family in Mexican culture and how it serves as a source of comfort and support for the characters is one of the main themes. To conclude, we can argue that "The House of Broken Angels" explores various identities, including those of the Mexican-American, the immigrant, the family member, and the aging. The novel portrays the complexities of identity and the challenges faced by those who are caught between two cultures or who are marginalized in society.

Процеси імміграції спонукають людину передумувати своє минуле і вибудовувати майбутнє з урахуванням тих кардинальних змін, що спричинені зміною локусу. Ідентичності, які формуються на чужині, заґрунтовані на діалозі рідної і нової культур; смислові акценти цих перемовин трансформуються як із віком іммігрантів, так і зі зміною поколінь. Творчість письменників, які представляють кілька культур, належить до транскультурного модусу письма. У ньому відбувається оприсутнення різних наративних форматів, перспектив персонажів, кількох мов, а також локусів. Усі це елементи дають можливість відійти від однозначних формулювань ідентичності та розкрити її амбівалентність. Транскультурний діалог між колективностями, репрезентований у творах письменників, які народилися чи виростали в одній культурі, а потім жили в іншій, доповнює і збагачує кожну з них. У романі Луїса Альберто Урреа "Будинок розбитих ангелів" ідентичності персонажів набувають різних осмислень залежно від їхнього походження і стосунку до родинної історії. У фокусі твору мексиканоамериканська родина, патріарх якої помирає від раку. Його порозуміння з усіма дітьми та молодшим братом визначає імпліцитний рівень художнього тексту. Тему подвійної ідентичності: мексиканської й американської розпрацьовано по-різному, залежно від покоління іммігрантів. Так, для першої генерації властиве прагнення довести своє право бути рівноправним членом американського суспільства, натомість представники другої хвилі намагаються розчинитися в новій спільноті й не надто задумуються над питаннями своєї належності. Особливе місце серед образів роману посідає Молодший Ангел, мати якого біла американка, а батько – мексиканець. Напруження, що існує між Молодшим Ангелом та родиною батька від першого шлюбу, розв'язується наприкінці твору. Порозуміння між братами через звернення до образу батька символізує примирення між різними ідентичностями, які мають право найперше бути собою.
ДІАЛОГИ ІДЕНТИЧНОСТЕЙ У РОМАНІ ЛУЇСА АЛЬБЕРТО УРРЕА "БУДИНОК РОЗБИТИХ АНГЕЛІВ"
Keywords: Luis Alberto Urrea; Mexican-American literature; The House of Broken Angels; immigrant identity; migration; Луїс Альберто Урреа; мексикано-американська література; роман; ідентичність іммігрантів; міграція